Grower Maturity Model for Perishable Supply Chain Improvement Under Competitive Environment - ชัชวาล เตละวาณิชย์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
In the era of globalization, the fast growing of humans being results in rapidly increasing demand of food and energy. Every country tries to explore the sources of food and energy to serve its own demand. The surplus of domestic demand will be exported. Importing countries also try to protect their local supplier by raising trade barrier and non-tariff trade barrier. The developed countries issue laws, regulations, and standards in order to protect and create advantages as well as to foster competitiveness for their domestic goods. The farmers in developing country try to implement follow the laws, regulation and standards of importing country. In agricultural industry, many methods and systems have been developed to support farming activities that focus on the exploitation of technological knowledge and enforcement of standards. However, the ability of farmers are the result of the education background, which is obstacle for fully utilization in daily agricultural processes. Costs and risks associated with agricultural business that cannot be managed effectively. This thesis presents the Grower Maturity Model (GMM) to the farmers, who are in the loop of supply chains to help farmers to improve productivity and control costs through improved risk management and the ability of farmers. The farmer can be classified into five groups as different of knowledge and capability level. Knowledge management theory applied to capture and disseminate explicit knowledge for increase capability of the farmers. New channels of knowledge transfer has presented. Agricultural Knowledge transferring is also different format depend on the contents of knowledge. The capacity of farmer is increased, resulting in better management of costs and risks throughout the supply chain. In this research have brought stakeholders for growing okra for export to Japan as a case study.